Nurses’ acceptance of total hospital information system (THIS) at Hospital Selayang / Noor’ain Mohamad Yunus, Dilla Syadia Ab Latiff and Zamzaliza Abdul Mulud - Mohamad Yunus, Noor’ain; Ab Latiff, Dilla Syadia; Abdul Mulud, Zamzaliza (Research Management Institute (RMI), 2011)
In Malaysia, Selayang Hospital has been the pioneer in the implementation of Total Hospital Information System (THIS) as an integrated care delivery system. However, shifting from the conventional method of reporting and organizing data and records using pen and paper to a computerized system was not an easy process. User’s acceptance and satisfaction play essential roles in the success of the system. The major problem with THIS is the system performance and capabilities which influence the level of acceptance and satisfaction among the users of THIS. Therefore, the primary concern of this study is to examine the role of THIS capability that mediates the relationship between system acceptance and users’ satisfaction. This cross-sectional study was conducted in the Selayang Hospital. Data were collected from participants who were nurses working in various disciplines in the hospital. Three hypotheses were formulated to guide this study. The findings suggest that perceived usefulness is related to system capability, perceived ease of use is related to system capability and nurses’ satisfaction and therefore all three hypotheses are supported. However, it is recommended that caution be taken in crediting the level of acceptance solely from predicting the capabilities and successfulness of a system. Other factors such as the users’ attitude, intention to use and the influence of trust towards the system should be further explored.